Three-dimensional evaluation of midfacial asymmetry in patients with nonsyndromic unilateral cleft lip and palate by cone-beam computed tomography - Choi, Youn-Kyung; Park, Soo-Byung; Kim, Yong-Il; Son, Woo-Sung (Korean journal of orthodontics (2012), 2013)
To compare three-dimensionally the midfacial hard- and soft-tissue asymmetries between the affected and the unaffected sides and determine the relationship between the hard tissue and the overlying soft tissue in patients with nonsyndromic complete unilateral cleft lip and palate (UCLP) by cone-beam computed tomography (CBCT) analysis. The maxillofacial regions of 26 adults (18 men, 8 women) with nonsyndromic UCLP were scanned by CBCT and reconstructed by three-dimensional dental imaging. The frontal-view midfacial analysis was based on a 3 × 3 grid of vertical and horizontal lines and their intersecting points. Two additional points were used for assessing the dentoalveolar area. Linear and surface measurements from three reference planes (Basion-perpendicular, midsagittal reference, and Frankfurt horizontal planes) to the intersecting points were used to evaluate the anteroposterior, transverse, and vertical asymmetries as well as convexity or concavity. Anteroposteriorly, the soft tissue in the nasolabial and dentoalveolar regions was significantly thicker and positioned more anteriorly on the affected side than on the unaffected side (p < 0.05). The hard tissue in the dentoalveolar region was significantly retruded on the affected side compared with the unaffected side (p < 0.05). The other midfacial regions showed no significant differences. With the exception of the nasolabial and dentoalveolar regions, no distinctive midfacial hard- and soft-tissue asymmetries exist between the affected and the unaffected sides in patients with nonsyndromic UCLP.